The Guidelines for the Academic Administration of the Schools under Lopburi Primary Educational Service Area Office 2: แนวทางการบริหารงานวิชาการของสถานศึกษาสำนักงานเขตพื้นที่ การศึกษาประถมศึกษาลพบุรี เขต 2 - chumim, waewta (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2020)
The purposes of this research were to study problems and find guidelines for the academic administration of the schools. The research method comprised 2 steps as follows; 1) To study the academic administration problems of the schools. The research sample was 306 school administrators and teachers. The research instrument was 5 rating scale questionnaires with the reliability at 0.97. The data were analyzed using standard statistics namely; frequency, percentage, mean and standard deviation. 2) To find guidelines for the academic administration of the schools under Lopburi Primary Educational Service Area Office 2. The research instrument was a focus group discussion record form and a focus group discussion with 7 experts was arranged. The research found that The academic administration problems of the schools overall were at an average level. The 3 aspects with the highest level were the development of media and technology for education, educational supervision, the learning resources development and the lowest level was the schools' curriculum development. The guidelines for the academic administration of the schools were schools should encourage teachers to use media technology in learning management by providing the media resources and supporting teachers to participate in media technology skills training. Moreover, the schools' educational supervision should be inspected and monitored. The schools should develop the learning resources by encouraging the community to participate. The schools should also encourage to use of the learning resources in classroom management and get the results to improve the curriculum so the teaching and learning would be relevant to the curriculum. The schools should evaluate the curriculum with the authentic assessment and organize the professional learning community (PLC) to develop students’ learning ability.